Vessel noise in spatially constricted areas: Modeling acoustic footprints of large vessels in the Cabot Strait, Eastern Canada. (15th August 2020) - Cominelli, Simone; Halliday, William D.; Pine, Matthew K.; Hilliard, R. Casey; Lawson, Jack W.; Duman, Nadia I.; Devillers, Rodolphe
Abstract: Large commercial vessel traffic is expected to continue growing over the next decades, making marine habitats noisier. This additional vessel noise could prevent the recovery of endangered marine species and populations and become a threat to others. Spatially constricted areas are places where both maritime traffic and species can concentrate, increasing the risks of negative impacts. We assessed sound amplitude and temporal trends in the daily movement of large ferries, container ships, bulkers, and tankers in the Cabot Strait, the main entrance way to the Gulf of St. Lawrence Seaway in Atlantic Canada. We used Automatic Identification System (AIS) and geophysical data as input for an acoustic model to produce 12 scenarios representing different regimes of vessel traffic and estimated equivalent continuous noise levels ( L eq ) over a 24-h period. Our results show that a 50% increase from the estimated median number of large vessel transits could lead to a 23% increase in the area affected by vessel noise, while doubling the number of transits could lead to a 58% increase. Cetaceans located <7–8 km from a vessel could experience sound pressure levels above the U.S. 120 dB re 1 μPa threshold for the onset of behavioral disturbance. Introducing speed restrictions could help reduce the acoustic footprint of the four vessel classes in this area and limit possible negative effects on marine mammals and other marine species. Graphical abstract: Image 1 Highlights: Large commercial vessel traffic has been growing in the Cabot Strait over the period 2013–2016. Cetaceans located < 7–8 km from a vessel in the study area can be affected by behavioral disturbance. Median levels of traffic can increase noise above background levels over 33% of the study area. Doubling merchant vessels traffic could lead to a 23% increase in the area affected by noise.